ANALISIS HUKUM ISLAM TERHADAP PEMBERDAYAAN MANAJEMEN TANAH WAKAF SEBAGAI PENGHASIL EKONOMI RAKYAT STUDI KASUS DI DESA PAOKMOTONG KECAMATAN MASBAGIK KABUPATEN LOMBOK TIMUR - Juliatin; Jumarim (Universitas Islam Negeri Mataram, 2021)
Ideally, waqf can be managed productively and developed into an Islamic institution that can improve people's welfare. In reality, together with zakat, waqf can be an instrument in poverty alleviation. Productive management of zakat cannot be separated from the media used in carrying out waqf. However, the practice that occurs in the field, especially in Paokmotong Village, Masbagik, East Lombok Regency, based on the results of initial observations conducted by researchers, waqf management is still around religious issues, considering that this has become a habit for the people of Lombok in particular. So, when there is waqf land, its management is often more for the needs of places of worship or the like. In fact, if developed, this could be an instrument in alleviating poverty like zakat.